2016
DOI: 10.1038/ejcn.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effects of an excessive folic acid intake

Abstract: Folate is a vital component of a healthy diet, being essential for numerous bodily functions. Deficiency of folate is common, with studies suggesting prevalence of deficiencyas high as 85.5% as was shown in women between the ages of 16 and 49, living in the UK. Causes of folate deficiency range from diet and lifestyle, to pathological and pharmacological processes. Because of the well-known role of folate in prevention of neural tube defects, numerous countries have implemented strategies to increase folate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 49 publications
(73 reference statements)
0
66
0
Order By: Relevance
“…Although it is controversial, long‐term unintentional effects of FA including various malignancies (colorectal, prostate and mammary), impaired cognitive function in elderly and masking of pernicious anaemia (Patel & Sobczyńska‐Malefora, 2017) mostly occur with high FA doses (>200 µg), in which chronic exposure of the liver to FA induces its saturation in the vascular system (Patanwala et al, 2014). Besides serious effects, risk of allergic reaction and findings of flushing, loss of appetite, nausea, bloating, bitter or bad taste in the mouth, depression, sleep problems and feeling excited are the less frequently reported short‐term effects of FA.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is controversial, long‐term unintentional effects of FA including various malignancies (colorectal, prostate and mammary), impaired cognitive function in elderly and masking of pernicious anaemia (Patel & Sobczyńska‐Malefora, 2017) mostly occur with high FA doses (>200 µg), in which chronic exposure of the liver to FA induces its saturation in the vascular system (Patanwala et al, 2014). Besides serious effects, risk of allergic reaction and findings of flushing, loss of appetite, nausea, bloating, bitter or bad taste in the mouth, depression, sleep problems and feeling excited are the less frequently reported short‐term effects of FA.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse outcomes of lifetime excess are still being investigated (see Ref. for proposed research priorities) and no clear consensus exists regarding the safety of high intakes of folic acid . Intake data from the United States and Mexico show that folic acid intake among young children approximates the UL (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Each nutrient is considered systematically, and any judgments or assumptions made are explicitly described in a discussion of the scientific uncertainties involved. 2,33 Risk assessment of nutrients follows four steps: 2 1,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] General value is divided by an uncertainty factor (UF), creating a buffer of safety to arrive at the UL (see discussion on NOAELs, LOAELs, CEs, and UFs below). Different ULs are set for different life-stage groups.…”
Section: Risk Assessment Modelmentioning
confidence: 99%
“…Positive effect of FA supplementation on the offspring neurodevelopment has been identified; in a large case‐cohort study, including 45,300 children, Levine et al, (2018) demonstrated that maternal exposure to FA before or during pregnancy was significantly associated with a low likelihood of autism spectrum disorder in the offspring. Some findings have pointed that normonutride women might have an excess of FA by the supplements and diet itself (Bailey et al, 2010; Patel and Sobczyńska‐Malefora, 2017; Selhub and Rosenberg, 2016). After the FA fortification regime in the US, it was identified an increase in FA intake that was approximately twice as large as previously projected (Choumenkovitch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%